Stress driven changes in the kinetics of bilayer embedded proteins: a membrane spandex and a voltage-gated sodium channel - Boucher, Pierre-Alexandre (Université d'Ottawa / University of Ottawa, 2011)
Bilayer embedded proteins are affected by stress. This general affirmation is, in this thesis, embodied by two types of proteins: membrane spandex and voltage-gated sodium channels. In this work, we essentially explore, using methods from physics, the theoretical consequences of ideas drawn from experimental biology. Membrane spandex was postulated to exist and we study the theoretical implications and possible benefits for a cell to have such proteins embedded in its bilayer. There are no specific membrane spandex proteins, rather any protein with a transition involving a large enough area change between two non-conducting states could act as spandex. Bacterial cells have osmovalve channels which open at near-lytic tensions to protect themselves against rupture. Spandex expanding at tensions just below the osmovalves’ opening tension could relieve tension enough as to avoid costly accidental osmovalve opening due to transient bilayer tension excursions. Another possible role for spandex is a tension-damper: spandex could be used to maintain bilayer tension at a fixed level. This would be useful as many bilayer embedded channels are known to be modulated by tension. The Stress/shear experienced in traumatic brain injury cause an immediate (< 2 min) and irreversible TTX-sensitive rise in axonal calcium. In situ, this underlies an untreatable condition, diffuse axonal injury. TTX sensitivity indicates that leaky voltage-gated sodium (Nav) channels mediate the calcium increase. Wang et al. showed that the mammalian adult CNS Nav isoform, Nav1.6, expressed in Xenopus oocytes becomes “leaky” when subjected to bleb-inducing pipette aspiration. This “leaky” condition is caused by a hyperpolarized-shift (left-shift or towards lower potentials, typically 20 mV) of the kinetically coupled processes of activation and inactivation thus effectively degrading a well-confined window conductance into a TTX-sensitive Na leak. We propose experimental protocols to determine whether this left-shift is the result of an all-or-none or graded process and whether persistent Na currents are also left-shifted by trauma. We also use modeling to assess whether left-shifted Nav channel kinetics could lead to Na+ (and hence Ca2+ ) loading of axons and to study saltatory propagation after traumatizing a single node of Ranvier.
Keywords: membrane; spandex; tension; membrane proteins; tension relief; voltage-gated sodium channel; trauma; Nav1.6; subthreshold oscillations; activation; inactivation; Nav channel; osmovalve; membrane trauma; nodes of Ranvier; left-shift